Correction: Replicating the Disease framing problem during the 2020 COVID-19 pandemic: A study of stress, worry, trust, and choice under risk. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0257151.].